8 specific Chinese herbal injections combined with chemotherapy for breast cancer: a systematic review and network meta-analysis of comparative safety and efficacy - Shi, Yunze; Cheng, Jianhao; Zhao, Yichen; He, Long; Duan, Lifeng; Wang, Huichao; Hu, Xiaoyang (Frontiers in Pharmacology, 2025)
BackgroundBreast cancer (BC) poses a major threat to human health. Since the beginning of the 21st century, numerous clinical studies conducted in China have reported the therapeutic advantages of combining Chinese herbal injections (CHIs) with chemotherapy; however, comparative evaluations of different CHIs remain scarce. This multidimensional network meta-analysis was designed to compare the efficacy of various CHIs and to identify the optimal combination regimen of CHI plus chemotherapy for breast cancer treatment.MethodsBy searching multiple databases, we screened randomized controlled trials (RCTs) on Chinese herbal injections (CHIs) combined with chemotherapy interventions for breast cancer (BC) from database inception to 25 October 2024. Studies meeting inclusion criteria with methodologically sound quality were included. Data analysis was performed using Stata 17.0 and R 4.2.1 software, with odds ratio (OR) and standardized mean difference (SMD) as effect size measures. The surface under the cumulative ranking curve (SUCRA) method was applied to rank the evaluated treatment regimens.ResultsThis network meta-analysis included 44 eligible RCTs, involving 3,982 patients and 8 CHIs. Shenqifuzheng Injection (SQFZ) combined with chemotherapy was most effective in enhancing the efficacy of chemotherapy, improving the quality of life of breast cancer patients, ameliorating the CD4+/CD8+ T-cell ratio, and inhibiting the decrease in white blood cell (WBC) count after chemotherapy. Compound Sophora Injection (FFKS) combined with chemotherapy performed best in increasing post - chemotherapy CD4+ and CD8+, lowering tumor marker CA125, and reducing post-chemotherapy platelet (PLT) and hemoglobin (HGB) declines. Kangai Injection (KA) combined with chemotherapy was most effective for CD3+ improvement. Kanglaite Injection (KLT) combined with chemotherapy had the best effect on reducing tumor markers CEA and CA153. Although a 2021 network meta-analysis (Comparative Efficacy and Safety of Chinese Herbal Injections Combined With Cyclophosphamide and 5-Fluorouracil Chemotherapies in Treatment of Breast Cancer: A Bayesian Network Meta-Analysis) examined chemotherapy combined with Chinese medicine injections for breast cancer, it was limited to the CF regimen and assessed few outcomes, with some lower-quality studies included (excluded herein). Our study improves methodology by incorporating high-quality RCTs across all chemotherapy regimens and evaluating multiple outcomes. This provides more comprehensive results, identifying SQFZ as most effective for improving response rate and Karnofsky Performance Status (KPS), thereby enhancing clinical utility.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier [CRD42024589306].